Radioprotective effects of a polysaccharide purified from Lactobacillus plantarum-fermented Ishige okamurae against oxidative stress caused by gamma ray-irradiation in zebrafish in vivo model. (January 2017) - Lee, WonWoo; Kang, Nalae; Kim, Eun-A.; Yang, Hye-Won; Oh, Jae-Young; Fernando, Ilekkuttige Priyan Shanura; Kim, Kil-Nam; Ahn, Ginnae; Jeon, You-Jin
Highlights: Fermentation by L. plantarum increased efficiency of carbohydrates of I. okamurae. An antioxidative polysaccharide (AP2) was purified from fermented I. okamurae. AP2 showed radio-protective effects on gamma ray-irradiated zebrafish model. AP2 contained a plentiful glucose and mannose composition. Abstract: In this study, the effects of a polysaccharide purified from the Celluclast extract of Lactobacillus plantarum -fermented Ishige okamurae (CPFI) against gamma ray-irradiation-induced oxidative stress were investigated in a zebrafish model. CPFI showed an increased extraction yield and high 1, 1-diphenyl-2-picrylhydrazyl and hydroxyl radical-scavenging activities. It was further purified using anion-exchange chromatography, and among the six fractions obtained, fraction 2 (AP2), with high glucose and mannose contents, exhibited the highest free radical scavenging activity. AP2 improved zebrafish survival and reduced malformations, such as yolk sac oedema and the occurrence of a bent tail. It also reduced cell death and the production of reactive oxygen species and nitric oxide in the zebrafish. Taken together, these results indicate that the AP2 polysaccharide has radioprotective and antioxidant effects, and is a value-added source of functional food ingredients.